Lactoferrin induces tropoelastin expression by activating the lipoprotein receptor‐related protein 1‐mediated phosphatidylinositol 3‐kinase/Akt pathway in human dermal fibroblasts. (8th September 2017) - Ryu, Mizuyuki; Nogami, Asuka; Kitakaze, Tomoya; Harada, Naoki; Suzuki, Yasushi A.; Yamaji, Ryoichi
Abstract: Dermal fibroblasts generate the extracellular matrix component elastin, which is synthesized as tropoelastin (TE) and play a critical role in maintaining skin elasticity. Lactoferrin (Lf), an 80‐kDa iron‐binding glycoprotein, has biological functions such as anti‐bacterial, ‐inflammatory, and ‐cancer activities. We previously reported that bovine Lf increases TE mRNA expression in human dermal fibroblasts. However, it remains unclear how Lf up‐regulates TE expression. Here, we investigated molecular mechanisms underlying this effect. Lf promoted the phosphorylation of Akt1 and extracellular signal‐regulated protein kinase (ERK)1/2. As expected, the phosphatidylinositol 3‐kinase (PI3K) inhibitor LY294002 and the MAPK inhibitor U0126 inhibited Lf‐induced phosphorylation of Akt1 and ERK1/2, respectively. In contrast, LY294002, but not U0126, inhibited Lf‐induced TE expression. Human dermal fibroblasts expressed lipoprotein receptor‐related protein 1 (LRP‐1) mRNA, and the LRP1 inhibitor receptor‐associated protein attenuated Lf‐induced increases in TE expression. Furthermore, siRNA‐mediated knockdown of LRP‐1 significantly suppressed Lf‐increased TE expression and Lf‐induced Akt1 phosphorylation. Iron‐saturated Lf (holo‐Lf) increased TE expression and promoted Akt1 phosphorylation, when compared to those parameters in cells treated with iron‐free Lf (apo‐Lf). Transforming growth factor (TGF)‐β1 also increased TE expression. LY294002 inhibited TGF‐β1‐mediated TE upregulation, whereas TGF‐β1 activated Akt2, but not Akt1, phosphorylation. These results indicate that holo‐Lf, but not apo‐Lf, increases TE expression through LRP‐1 in human dermal fibroblasts and suggest that holo‐Lf and TGF‐β1 enhance TE expression by activating the PI3K/Akt1 and PI3K/Akt2 pathways, respectively.